Gingival Challenges in Parry-Romberg Syndrome: A Multidisciplinary Approach to Oral Health Management - Singh, Akanksha; Rathore, Praveen Kumar; Singh, Pushpendra; Khulbe, Kavya; Singh, Rika (Update Dental College Journal, 2024)
Background: Parry-Romberg Syndrome (PRS), characterized by progressive hemifacial atrophy, presents unique challenges in oral health management due to its rare nature and varied clinical manifestations. While cutaneous and craniofacial features are well-documented, gingival involvement is less commonly recognized. Case Presentation: We present a case of gingival manifestation of PRS in a 26-year-old female, emphasizing the progressive nature of the condition and its impact on oral health. Clinical examination revealed significant gingival recession on the affected side, leading to tooth sensitivity and compromised periodontal health. Diagnosis: The diagnosis of PRS was established based on characteristic facial asymmetry, radiographic findings, and absence of systemic involvement. Gingival recession was confirmed through periodontal assessment. Management: Management strategies included symptomatic relief with desensitizing toothpaste, preservation of periodontal health through oral hygiene instructions and periodontal therapy, and supportive care tailored to the patient's needs. Multidisciplinary collaboration was essential to optimize patient care and address the complex clinical manifestations of PRS. Outcome: While complete resolution of gingival recession was not achieved due to the progressive nature of PRS, symptomatic relief and preservation of periodontal health were achieved through comprehensive management strategies. Long-term follow-up is essential to monitor disease progression and adjust treatment as needed. Conclusion: Gingival involvement in PRS underscores the importance of a multidisciplinary approach to oral health management. Recognition of gingival manifestations and implementation of individualized treatment plans are crucial for optimizing oral health outcomes and enhancing the quality of life for affected individuals. Update Dent. Coll. j: 2024; 14(2): 27-30